Good governance: a role for organizational politics and organizational democracy in creating moral communities - Butcher, David; Clarke, Martin (Elsevier, 2012)
Accusations of irresponsible trading have been leveled at the financial services sector in the aftermath of the global economic downturn of the last three years. In turn, this has led to calls for even greater regulation and public scrutiny of board decisions. Yet why should these be necessary? After all, the corporate world was changed by the comprehensive overhaul of governance practices that followed the scandals of Enron, WorldCom and others, now a decade ago. The answer is a stark indication of the limits to hierarchical control that exist in today's organizations. It is clear from the autopsies of sub-prime lending casualties like Lehman Brothers, Fannie Mae, and Freddie Mac that boards cannot simply require that good governance is practiced within their organizations. Yet this should not be of surprise. For failure to take account of differing stakeholder interests is unlikely to be effective in encouraging responsible corporate behaviour.